THE FLOUTING MAXIMS IN THE MAIN CHARACTERS’ UTTERANCES OF WE BOUGHT A ZOO MOVIE - HASANI, MERIAM (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Cooperative Principle, Flouting Maxims, We Bought A Zoo movie People use language to communicate with others in their society. They use it to express their ideas, thoughts, messages in a conversation. One way to make the conversation becomes successful is by fulfilling The Cooperative Principle by Grice (1989). There are four maxims which need to be fulfilled in the principles namely, maxim of quantity, maxim of quality, maxim of relation, and maxim of manner. However, in reality people sometimes disobey the maxims, and when they do that, it means that they are flouting the maxims. When flouting maxim happens, there will be implicature arises. It is an implied or intended meaning from a speaker’s utterance that is expected to be understood by the hearer. The writer conducts a study about flouting maxim in We Bought A Zoo movie. There are two problems to be solved in the study, namely: (1) What maxims are flouted in the main character’s utterances in We Bought A Zoo movie (2) What intended meaning of the utterances are being flouted by the main characters on We Bought A Zoo movie.This study uses qualitative approach since the data are in the form of words rather than number or statistics. In this study the data are the utterances of the main characters which contain flouting maxims. The data are collected and analyzed based on the theory of Cooperative Principle by Grice (1989).The result of this study reveals that all the maxims are flouted in the main character’s utterances. The intended meaning of the utterances being flouted are to emphasize a point in a conversation, to express a burden in doing something, to force someone to do something, to mock a character’s behaviour, to decline an intention, to make a joke, to hide the truth, change the subject of conversation, to give opinion, and to refuse an order.The writer suggests the next researcher to explore more about the objectives of the study such as by identifying the reason in flouting the maxim or by trying to analyze whether there is any correlation between a character’s personality or traits with their tendency to do flouting maxim in their communication.